Safety profile of the 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) - Sven Arne Silfverdal; Vanessa Coremans; Nancy François; Dorota Borys; Jan Cleerbout (Taylor & Francis Group, 2017)
Safety and reactogenicity data were reviewed following 10 years of experience with the 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) in clinical development and from post-licensure settings. Analyses of pooled clinical trial data and post-marketing reports provided an overview of its safety profile and allowed assessment of rare adverse events that might not have been identified previously. The safety of PHiD-CV was also evaluated in children at higher risk for pneumococcal infection (preterm and HIV-infected or HIV-exposed infants), for different vaccination schedules and co-administered pediatric vaccines, and with a focus on special categories of adverse events (febrile convulsions, apnea, Kawasaki disease and sudden deaths). Following the distribution of over 235 million doses, PHiD-CV has been well tolerated when co-administered with other pediatric vaccines to children aged less than 5 years from diverse ethnic and geographic backgrounds. Detailed examination of various aspects has confirmed its favorable benefit: risk profile.